2004
DOI: 10.1093/jac/dkh317
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and molecular characterization of macrolide and streptogramin resistance in Streptococcus mitis from neutropenic patients

Abstract: The prevalence of macrolide resistance is high in S. mitis from neutropenic patients and is due to the spread of ermB- or mefA-like genes alone or combined. Resistance to streptogramins is rare and in this case associated with ribosomal mutation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…This study also revealed a relatively high percentage (42%) of macrolidenonsusceptible VGS within the healthy population. Moreover, 70.0% of macrolide-nonsusceptible clinical isolates were presented in a Tunisian study [47]. Moreover, 70.0% of macrolide-nonsusceptible clinical isolates were presented in a Tunisian study [47].…”
Section: Antibiotic Resistancementioning
confidence: 96%
“…This study also revealed a relatively high percentage (42%) of macrolidenonsusceptible VGS within the healthy population. Moreover, 70.0% of macrolide-nonsusceptible clinical isolates were presented in a Tunisian study [47]. Moreover, 70.0% of macrolide-nonsusceptible clinical isolates were presented in a Tunisian study [47].…”
Section: Antibiotic Resistancementioning
confidence: 96%